Digital Marketing in an Effort to Increase Customer Satisfaction Through Company Image: A Conceptual Study as a Guide for Researchers - Fatima, Arlindo Do Ceu; Gupron, Gupron (Dinasti Publisher, 2024)
The issue of customer satisfaction is the focus of attention of stakeholders (government, business people, suppliers, consumers and so on). This is due to their better understanding of the concept of satisfaction as a strategy to win increasingly fierce business competition. In this case, customer satisfaction is important for business owners and managers because customers will pass on information about their expectations to other potential customers, which will then increase the company's integrity. This research consists of several parts. First, the literature review focuses on orientation to the digital marketing concept. Second, the research model and propositions developed in this study are based on a literature review of previous studies, such as the relationship between digital marketing and customer satisfaction, both directly and indirectly through the company's image. Based on studies conducted through theory and previous research, it can be concluded that digital marketing has an influence on customer satisfaction, both directly and indirectly through the company's image.